2019
DOI: 10.1088/1742-6596/1424/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent LPG Gas Leak Detection Tool with SMS Notification

Abstract: Gas is a molecule that is not bound, formless, invisible and can turn into search or solid at certain temperature pressures. LPG gas is one of the needs for industry and household needs, namely for cooking. LPG gas in Indonesia is the cause of many fires, a factor that often causes LPG gas fires is a damaged gas regulator. Therefore prevention and security are needed to minimize fires. Seeing this and given the technological developments, an intelligent Arduino-based device was created that was able to overcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Using that contact, we switch off Essential findings of others in this field: several research works are found over the net. Hasibuan et al (2019). [1] demonstrate a project where LPG is detected using an intelligent system, and once it is detected, it sends the notification as an SMS to the mobile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using that contact, we switch off Essential findings of others in this field: several research works are found over the net. Hasibuan et al (2019). [1] demonstrate a project where LPG is detected using an intelligent system, and once it is detected, it sends the notification as an SMS to the mobile.…”
Section: Introductionmentioning
confidence: 99%
“…Hasibuan et al (2019). [1] demonstrate a project where LPG is detected using an intelligent system, and once it is detected, it sends the notification as an SMS to the mobile. The researchers (Hussien et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia is a developing country that much empowers energy sources, especially fossil energy, namely petroleum [1]. Indonesian people still use LPG as a necessity in households and businesses; mostly, it is used to cook household needs and restaurant management [2]. However, the existence of petroleum has been reduced, so it would be replaced by natural resources that are still abundant, for example, natural gas energy.…”
Section: Introductionmentioning
confidence: 99%